Development of emotional competencies in Chilean elementary school students through the HAPPY 8-12 Program - Lagos San Martín, Nelly (2021)
HAPPY 8 to 12 is a program created in Spain that encourages assertive conflict resolution. The purpose of this article was to evaluate the effectiveness of “HAPPY 8-12” in Chile. The study was carried out from a quasi-experimental design with pre and post-test and control group, applying Analysis of Variance of Repeated Measures to determine the effectiveness of the program. The Socio-Emotional Competence Assessment (ECSE) scale was used to evaluate 197 primary school students (3rd to 6th year), of them 96 are men and 101 women, their ages fluctuate between 8 and 12 years. The results show positive modifications in the students belonging to the experimental group, which allows us to maintain that this program has been able to respond to an existing training need in the Chilean educational system.